Ruling 84(56/1): Personal Financing-i Umrah & Travels - Soualhi, Younes; Zakariyah, Habeebullah; Ashurov, Sharofiddin; Ishak, Muhammad Shahrul Ifwat; Saleh, Abdulmajid Obaid Hasan (Al Rajhi Bank Malaysia, 2025)
The Shariah Board of Al Rajhi Banking & Investment Corporation (Malaysia) Bhd (the “Shariah Board”) in its recent meeting held on 09/07/1446 H. corresponding to 09/01/2025 G. reviewed a proposal concerning “Personal Financing-i Umrah & Travels” submitted by the Bank.